Network disruption detected in PK (Pakistan) - Voidly (2026)
CRITICAL severity disruption detected in Pakistan. Confidence: 70%. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: PK-2026-0008
Keywords: internet disruption; PK; disruption; critical